Information Assurance in Saudi Organizations – An Empirical Study - Nabi, Syed Irfan; Mirza, Abdulrahman A.; Alghathbar, Khaled (Security Technology, Disaster Recovery and Business Continuity, 2010)
This paper presents selective results of a survey conducted to find out the much needed insight into the status of information security in Saudi Arabian organizations. The purpose of this research is to give the state of information assurance in the Kingdom and to better understand the prevalent ground realities. The survey covered technical aspects of information security, risk management and information assurance management. The results provide deep insights in to the existing level of information assurance in various sectors that can be helpful in better understanding the intricate details of the prevalent information security in the Kingdom. Also, the results can be very useful for information assurance policy makers in the government as well as private sector organizations. There are few empirical studies on information assurance governance available in literature, especially about the Middle East and Saudi Arabia, therefore, the results are invaluable for information security researchers in improving the understanding of information assurance in this region and the Kingdom.